2022
DOI: 10.3390/ijms231911774
|View full text |Cite
|
Sign up to set email alerts
|

Putative Transcription Factor Genes Associated with Regulation of Carotenoid Biosynthesis in Chili Pepper Fruits Revealed by RNA-Seq Coexpression Analysis

Abstract: During the ripening process, the pericarp of chili pepper (Capsicum spp.) fruits accumulates large amounts of carotenoids. Although the carotenoid biosynthesis pathway in the Capsicum genus has been widely studied from different perspectives, the transcriptional regulation of genes encoding carotenoid biosynthetic enzymes has not been elucidated in this fruit. We analyzed RNA-Seq transcriptomic data from the fruits of 12 accessions of Capsicum annuum during the growth, development, and ripening processes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…On the contrary, the ripening process of pepper fruits involves many changes at the phenotypic, transcriptomic, proteomic, and metabolomic levels, and its big genome size, in comparison to other Solanaceae, makes its analysis complex (Dyachenko et al 2020 ; Razo-Mendivil et al 2021 ; Esposito et al 2022 ; Kovács et al 2022 ; Del Giúdice et al 2023 ). Recently, “omic” approaches have been carried out to study specific aspects of the ripening process (Chiaiese et al 2019 ; Dubey et al 2019 ; Zuo et al 2019 ; Lopez-Ortiz et al 2021 ; Rödiger et al 2021 ; Momo et al 2022 ; Villa-Rivera et al 2022 ; Song et al 2022 ; Liu et al 2023 ; Wang et al 2024 ) which are dependent on the variety, environmental growth conditions, fruit position, and ripening stage (Ribes-Moya et al 2020 ; Jang et al 2022 ; Lahbib et al 2023 ; Guijarro-Real et al 2023 ; Islam et al 2023 ). Despite the increase in information on the ripening of pepper fruits, to our knowledge, there is no data on the LAP in this process.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the ripening process of pepper fruits involves many changes at the phenotypic, transcriptomic, proteomic, and metabolomic levels, and its big genome size, in comparison to other Solanaceae, makes its analysis complex (Dyachenko et al 2020 ; Razo-Mendivil et al 2021 ; Esposito et al 2022 ; Kovács et al 2022 ; Del Giúdice et al 2023 ). Recently, “omic” approaches have been carried out to study specific aspects of the ripening process (Chiaiese et al 2019 ; Dubey et al 2019 ; Zuo et al 2019 ; Lopez-Ortiz et al 2021 ; Rödiger et al 2021 ; Momo et al 2022 ; Villa-Rivera et al 2022 ; Song et al 2022 ; Liu et al 2023 ; Wang et al 2024 ) which are dependent on the variety, environmental growth conditions, fruit position, and ripening stage (Ribes-Moya et al 2020 ; Jang et al 2022 ; Lahbib et al 2023 ; Guijarro-Real et al 2023 ; Islam et al 2023 ). Despite the increase in information on the ripening of pepper fruits, to our knowledge, there is no data on the LAP in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, transcriptional studies have been focused on just early or late stages of fruit development and ripening (Ando et al, 2012;Goḿez et al, 2014;Liu et al, 2017), or on a specific tissue (Parra et al, 2013;Tafolla-Arellano et al, 2017;Luo et al, 2018;Zhang et al, 2021;Zhou et al, 2022), or even on cell transcriptomics (Martin et al, 2016;Shinozaki et al, 2018). Moreover, transcriptomics of hormones-related gene expression (Zhu et al, 2011;Huang et al, 2014;Van de Poel et al, 2014;Tang et al, 2015;Briegas et al, 2020;Kou et al, 2021;Qiao et al, 2021;Camarero et al, 2023), or the effects of environmental/ stress factors on fruit gene expression (Li et al, 2019;Cramer et al, 2020;Waite et al, 2023), biosynthesis/metabolism genes expressed during fruit development (Yu et al, 2021;Zhang et al, 2021;Diao et al, 2023), transcriptomic changes due to the evolution/domestication processes (Martıńez et al, 2021;Borredáet al, 2022;Gramzou et al, 2022), expression of transcription factors genes and gene networks (Ye et al, 2015;Villa-Rivera et al, 2022), transcriptomics of fruit quality (Yang H, et al, 2021;Lei et al, 2022), fruit shape (Tsaballa et al, 2011;Shi et al, 2023) and size-related genes (Huang et al, 2023;Liu et al, 2023), or postharvest transcriptomic changes (Wang et al, 2018;Romero et al, 2022), have been do...…”
Section: Fruit Transcriptomicsmentioning
confidence: 99%
“…Villa-Rivera et al compared the expression changes of carotenoid biosynthesis genes between the fruits of 12 chili pepper accessions during the development and ripening processes. They identified the relevant transcription factor for carotenoid biosynthesis by coexpression analysis [17]. By combining comparative genomics and expression pattern analysis with VIGS, subcellular localization, yeast one-hybrid, and dual-luciferase reporter assays, Liu et al systematically identified members of the CaMYBrelated family, predicted their possible biological functions, and revealed that CaMYB37 is critical for the transcriptional regulation of capsaicin biosynthesis in peppers [18].…”
mentioning
confidence: 99%